Effects of a Mixed Reality-based Cognitive Training System Compared to a Conventional Computer-assisted Cognitive Training System on Mild Cognitive Impairment: A Pilot Study. Issue 3 (September 2019) - Park, Eunhee; Yun, Byoung-Ju; Min, Yu-Sun; Lee, Yang-Soo; Moon, Sung-Jun; Huh, Jae-Won; Cha, Hyunsil; Chang, Yongmin; Jung, Tae-Du
Abstract : Background: Mixed reality (MR) technology, which combines the best features of augmented reality and virtual reality, has recently emerged as a promising tool in cognitive rehabilitation therapy. Objective: To investigate the effectiveness of an MR-based cognitive training system for individuals with mild cognitive impairment (MCI). Methods: Twenty-one individuals aged 65 years and older who had been diagnosed with MCI were recruited for this study and were divided into two groups. Participants in the MR group (n=10, aged 70.5±4.2 years) received 30 minutes of training 3 times a week for 6 weeks using a newly developed MR-based cognitive training system. Participants in the control group (n=11, aged 72.6±5.3 years) received the same amount of training using a conventional computer-assisted cognitive training system. Both groups took the Korean version of the Consortium to Establish a Registry for Alzheimer's Disease (CERAD-K) both before and after intervention. To determine the effect of the intervention on cognitive function, we compared the difference in each group's CERAD-K scores. Results: There was a statistically significant interaction between intervention (MR group vs control group) and time (before vs after intervention) as assessed by the Constructional Recall Test. The individuals with MCI who participated in the MR training showed significantly improved performance in visuospatial working memory compared with the individuals with MCI who participated in the conventional training. Conclusion: An MR-based cognitive training system can be used as a cognitive training tool to improve visuospatial working memory in individuals with MCI.